The Two Medieval Congregations of Las Huelgas de Burgos (Edad Media. Revista de Historia, 2024)
This research provides a new analysis of the documentation of the Abbey of santa Maria la Real de Las Huelgas at Burgos and of the Cistercian nunneries under its authority between 1187 and 1540. The institution they had formed was much more unstable than previously thought. Two distinct congregations can be distinguished. The first was theoretically created in 1189 and was legally effective in the 13th century, but had no concrete effects. The second was created anew in the 1370s, with other members, and grew throughout the period under study. It did have effects, particularly in the election of abbesses.
Keywords: Las Huelgas de Burgos; Cistercian Nuns; congregation of Las Huelgas; filiations; chapter of abbesses of Las Huelgas